PROPOSALS FOR INTERNATIONAL CO OPERATION IN THE COLLECTION OF PLANTING MATERIAL AND IN COMPARATIVE TRIALS OF COCONUT HYBRIDS - M. de NUCE de LAMOTHE; J.P. LE SAINT (International Coconut Community Journal, 1985)
The genetic improvement of coconut is clifficult and costly for numerous reasons of which the chief ones are related to its biology the length of the unproductive phase and the interval between generations, the low multiplication rate and the lack of an asexual mode of reproduction, the size and weight of its seed and the absence of dormancy, the bulk of the tree and low planting density. In most countries, the means provided to researchers were and still are very limited, partly perhaps because coconut has remained essentially a smallholding tree and the private plantation sector has taken relatively little interest in it.